Challenging process to make the Lateglacial tree-ring chronologies from Europe absolute: an inventory - Kaiser, Klaus F.; Friedrich, Michael; Kromer, Bernd; Boeren, Ilse; Remmele, Sabine; Guibal, Frédéric (Quaternary science reviews, 2012)
Here we present the entire range of Lateglacial tree-ring chronologies from Switzerland, Germany, France, covering the Lateglacial north and west of the Alps without interruption as well as finds from northern Italy, complemented by a 14C data set of the Swiss chronologies. Geographical expansion of cross-matched European Lateglacial chronologies, limits and prospects of teleconnection between remote sites and extension of the absolute tree-ring chronology are discussed. High frequency signals and long-term fluctuations are revealed by the ring-width data sets of the newly constructed Swiss Late-glacial Master Chronology (SWILM) as well as the Central European Lateglacial Master Chronology (CELM) spanning 1606 years. They agree well with the characteristics of Boelling/Alleroed (GI-1) and the transition into Younger Dryas (GS-1). The regional chronologies of Central Europe may provide improved interconnection to other terrestrial or marine high-resolution archives. Nevertheless the breakthrough to a continuous absolute chronology back to Boelling (GI-1e) has not yet been achieved. A gap remains, even though it is covered by several floating chronologies from France and Switzerland.
Gesehen am 16.07.2018
Published online: 23 August 2010